Improvement in dysmyelination by the inhibition of microglial activation in a mouse model of Sandhoff disease. Issue 11 (1st August 2018) - Ogawa, Yasuhiro; Irisa, Masahiro; Sano, Takafumi; Yanagi, Yusuke; Furusawa, Eiri; Saito, Takahiro; Yamanaka, Shoji; Itoh, Kohji; Sakuraba, Hitoshi; Oishi, Kazuhiko
Abstract : Sandhoff disease (SD) is a genetic disorder caused by a mutation of the β-subunit gene β-hexosaminidase B (HexB) in humans, which results in the massive accumulation of the ganglioside GM2 and related glycosphingolipids in the nervous system. SD causes progressive neurodegeneration and changes in white matter in human infants. An animal model of SD has been established, Hexb -deficient ( Hexb −/− ) mice, which shows abnormalities resembling the severe phenotype found in human infants. Previously, we reported that the activation state of microglia caused astrogliosis in the early stage of Hexb −/− mouse development. To study how the symptoms of SD develop, we explored the difference in gene expression between 4-week-old Hexb +/− and Hexb −/− mouse cerebral cortices by microarray analysis. The data indicated not only the upregulation of immune system-related genes but also the downregulation of myelin-related genes in the 4-week-old Hexb −/− mouse cerebral cortices. To test the correlation between inflammation and dysmyelination, we generated double-knockout mice of Hexb −/− and the Fc receptor γ gene ( Fcrγ −/− ), which is a regulator of autoimmune responses. Dysmyelination recovered in these double-knockout mice. The number of oligodendrocyte progenitors, which expressed platelet-derived growth factor receptor-α, did not change in the 2-week-old mouse brain. These results indicate that microglial activation plays an important role in the myelination process, without influencing the number of oligodendrocyte progenitors, in the development of Hexb −/− mice.